Pengembangan Multimedia Interaktif Materi Pemrograman Dasar Untuk Siswa Kelas X Jurusan Multimedia SMK Nasional Malang Dengan Menggunakan Model APPED - Hosea Scarlet Haholongan; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In Indonesia has demanded competitiveness to face the competition. One such competition is the fulfillment of human resources in vocational education development. There are so many vocational schools in Indonesia, one of which is National Vocational High School Malang. Based on the results during Praktik Pengalaman Lapangan (PPL), this school has not yet developed modules or media. The solution to these problems is to develop interactive multimedia with APPED model with the initial stages of analysis until dissemination. For an ongoing evaluation with three aspects of certain assessments have all worked well. Then the results of alpha testing are 83.5% and 72.5%. After that the results of beta testing are 85% by student responses. For the dissemination, pre-test and post-test experiments were conducted. The average for pre-test score is 54, and the average for post-test score is 87, which means that there is an increase before and after the interactive learning multimedia is tested. For the normality test in the pre-test is 0.27, the post-test is worth 0.33. All normality test values ​​are more than 0.05 so the distribution is normal. For the t test it is worth 0,000 which means it is less than 0.05. So for the t test, there is a difference in the average value between the results of the pre-test and post-test. From all validations and tests, it can be concluded that Interactive Multimedia Learning is feasible to use in the learning process.